Patients' experiences and reported barriers to colonoscopy in the screening context--a systematic review of the literature. - McLachlan, SA; Clements, A; Austoker, J (2012)
OBJECTIVE: A systematic review of the literature was conducted to characterise patients' own experience of colonoscopy in the screening context. METHODS: A search strategy was applied in MEDLINE, EMBASE and PSYCHinfo (1996-2009). Thematic analysis and narrative summary techniques were used. RESULTS: Fifty-six studies met eligibility criteria and were included in the analysis. Seven studies examined patients' views after having colonoscopy. Forty-seven studies addressed patient-reported barriers to an anticipated primary colonoscopy. Most patients perceived the laxative bowel preparation to be the most burdensome part of colonoscopy. Other reported difficulties included anxiety, anticipation of pain, feelings of embarrassment and vulnerability. Inadequate knowledge and fear of finding cancer were identified as obstacles to the uptake of screening colonoscopy. Physician endorsement, having a family history, knowing someone with cancer, and perceived accuracy of the test were incentives to having a colonoscopy. Two studies focused on colonoscopy after faecal occult blood screening. Similar procedural, personal, and practical concerns were reported. CONCLUSIONS: Bowel preparation, lack of awareness of the importance of screening, and feelings of vulnerability in women are all significant barriers to screening colonoscopy. PRACTICE IMPLICATIONS: Patient reported obstacles and barriers to screening colonoscopy needs to be addressed to improve adherence.